2017
DOI: 10.1016/j.srhc.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Trends and consequences of the technocratic paradigm of childbirth in Portugal: A population-based analysis of birth conditions and social characteristics of parents

Abstract: Limiting the study of childbirth to its medical aspects leaves important dimensions out of the analysis: women's perception of birth-related risks associated with the medicalised offer of maternity care, and the implications of this childbirth paradigm for health outcomes and for future care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 38 publications
4
16
0
2
Order By: Relevance
“…Furthermore, due to legislation home births are only available in Portugal through private healthcare [39], which widens economic inequality of access to a woman's chosen care during birth. One study found that home births, as well as more "alternative" forms of care, were more common among women of a higher social class, with a higher level of education and more resources [23]. Until 1961, 80% of births in Portugal were home births, a trend which continued into the 1970s.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, due to legislation home births are only available in Portugal through private healthcare [39], which widens economic inequality of access to a woman's chosen care during birth. One study found that home births, as well as more "alternative" forms of care, were more common among women of a higher social class, with a higher level of education and more resources [23]. Until 1961, 80% of births in Portugal were home births, a trend which continued into the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of home birth as an option for public healthcare users is one factor in the highly medicalized state of pregnancy and birth in Portugal, and the movement towards this medicalized state has been well documented [35,39]. In 2010 and 2011, 99% of births in Portugal took place in a hospital [23]. The presence of doctors at birth has been increasing while the presence of obstetric and non-obstetric nurses has been decreasing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, higher income women tend to deliver in private (rather than public) hospitals. It remains unclear whether physicians in public hospitals would entertain the request by immigrant mothers (such as Brazilian‐born women) to have a caesarean delivery . In addition, explanations for the upward shift in maternal educational attainment, especially after the global economic crisis, would benefit from understanding educational policies as well as the financial cost of university education in Portugal.…”
mentioning
confidence: 99%